Regulation for startups in Indonesia: Problems and recommendations - Acep Rohendi; Asriani Asriani; Dona Budi Kharisma (Cogent Business & Management, 2023)
The rapid growth of the digital economy in Indonesia provides a positive trend for startups. The valuation of Indonesia's digital economy is the highest in Southeast Asia. This paper aims to identify problems and legal issues regarding startups. This research also tries to formulate regulations that can support the development of startups in Indonesia. The data collection technique used is library research by examining books, journals, reports, and laws related to startups. The data analysis technique used is the legal norm method by analyzing laws and regulations related to startups. Based on the results of the research, it was found that startups in Indonesia still face various legal problems such as the absence of startup regulations and the complicated and lengthy startup licensing process. Based on these problems, it is recommended that Indonesia has regulations that specifically regulate startups. The regulation regulates the process of facilitating business licensing for startups, financial support and capital raising schemes. To overcome these problems, Indonesia needs to reformed regulations in the startup sector and apply the licensing concept through a risk-based approach.
Keywords: 650; digital economy; regulation; risk-based approach; startup